Simulation on Stern-Rudder Independent Control for Submarine Motion in a Vertical Plane - Ying Xiong; Jie Hu Jun (Cybernetics and Information Technologies, 2015)
To independently control the depth and trim of the submarine, a fuzzy control method on stern-rudder is proposed, and the advantage of a single stern-rudder in low noise control is elaborated. Taking into account the character of the single stern-rudder, a fuzzy controller is designed. The simulation results have shown that the algorithm has very good control precision, which decreases the rudder and radiated noise greatly.